Taking it with a grain of salt and pepper: Spared and impaired use of contextual information in the language production of people with schizophrenia - Sharpe, Victoria. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2023.; Submitted to the Dept. of Psychology.; Advisor: Gina Kuperberg.; Committee: J.P. de Ruiter, Eric Tan, Lena Palaniyappan, and Lin Wang.; Keywords: Psychology, and Cognitive psychology.